Project 30 Task Force Report (2008)
The Project 30 Task Force was formed in mid-October by USATF CEO Doug Logan to impartially evaluate USATF High Performance Programs, analyze Team USA Performance in Beijing, and chart a course for programmatic change to maximize Team USA performance in Olympic and World Championship competition. Initially dubbed the USATF High Performance Audit Panel, its members were selected by Mr. Logan in consultation with varied individuals throughout the sport. His stated goal was to choose individuals who weren`t directly involved in preparing or coaching the 2008 Olympic Team. Renamed the Project 30 Task Force following Mr. Logan`s goal of 30 medals at the 2012 Olympic Games in London, which he made public on December 7, 2008, the Project 30 Task Force is composed of Carl Lewis, Benita Fitzgerald Mosley, Ralph Mann, Mel Rosen, Aretha Hill Thurmond and Deena Kastor. (Ms. Thurmond and Ms. Kastor joined the panel in early December.) The USOC nominated to the Task Force Steve Roush, Doug Ingram and Jay Warwick, making the Task Force a nine-person group. (See Appendix A - Project 30 Task Force members.) USATF Director of Communications Jill Geer was designated as Administrator to the Task Force.